Johnson, The Early American Republic, 1789-1826 - McIlhenny, Ryan (Teaching History: A Journal of Methods, 2007)
Paul Johnson, professor of history at the University of South Carolina and author of a number of highly acclaimed works including A Shopkeeper’s Millennium, has offered a fresh survey of the American republic’s early and arguably most critical developmental period. Chapters I and 2 focus on the heated political debates between the commercial-industrial Federalists and the democrat-agrarian Jeffersonians over the most beneficial program to steer the course of the young nation. Such disputes laid the groundwork for American party politics.